Renal tumour nephrometry score does not correlate with the risk of radiofrequency ablation complications. (4th November 2013) - Seideman, Casey A.; Gahan, Jeffrey; Weaver, Matthew; Olweny, Ephrem O.; Richter, Michael; Chan, Danny; Cadeddu, Jeffrey A.
Abstract : Objectives: To assess whether the R.E.N.A.L. nephrometry score (consists of [R]adius [tumour size as maximal diameter], [E]xophytic/endophytic properties of the tumour, [N]earness of tumour deepest portion to the collecting system or sinus, [A]nterior [a]/posterior [p] descriptor and the [L]ocation relative to the polar line) is associated with complication risk in patients that have radiofrequency ablation (RFA) for small renal masses (SRMs). To evaluate a standardised system for predicting complication risks which has not been studied. Patients and Methods: We reviewed the records of all patients who underwent RFA at our institution between May 2001 and May 2011. RFA was performed using a temperature‐based system and a 25‐G nine‐tine array needle probe. Patients with preoperative imaging available for R.E.N.A.L. nephrometry scoring were included. R.E.N.A.L. composite scores, tertile stratification and preoperative patient characteristics were analysed for significance in relation to complications. Complications were defined using the Clavien‐Dindo classification system. Results: In all, 199 patients had preoperative R.E.N.A.L. nephrometry scores available; 170 underwent percutaneous RFA and 29 laparoscopic RFA. The mean (range) American Society of Anesthesiologists (ASA) score was 2.6 (1–4). The mean (range) tumour size was 2.4 (0.7–5.4) cm. Overall, 14 complications were identified; 10 minor (Clavien I–II) and four major (Clavien III–IV). There was no significant association between complications and R.E.N.A.L. nephrometry score, R.E.N.A.L. nephrometry tertiles, tumour diameter, tumour location or ASA score ( P > 0.05). Conclusion: R.E.N.A.L. nephrometry scoring fails to predict complications of RFA for SRMs when using a temperature‐based nine‐tine array probe.